Reversion of Steatosis by SREBP-1c Antisense Oligonucleotide did not Improve Hepatic Insulin Action in Diet-induced Obesity Mice - Vitto, M. F.; Luz, G.; Luciano, T. F.; Marques, S. O.; Souza, D. R.; Pinho, R. A.; Lira, F. S.; Cintra, D. E.; De Souza, C. T. (Hormone and Metabolic Research, 2012)
The literature has associated hepatic insulin action with NAFLD. In this sense, treatments to revert steatosis and improve hepatic insulin action become important. Our group has demonstrated that inhibition of Sterol Regulatory Element Binding Proteins-1c (SREBP-1c) reverses hepatic steatosis. However, insulin signals after NAFLD reversion require better investigation. Thus, in this study, we investigated if the reversal of NAFLD by SREBP-1c inhibitor results in improvement in the hepatic insulin signal in obesity mice. After installation/achievement of diet-induced obesity and insulin resistance, Swiss mice were divided into 3 groups: i) Lean, ii) D-IHS, diet-induced hepatic steatosis [no treatment with antisense oligonucleotide (ASO)], and iii) RD-IHS, reversion of diet-induced hepatic steatosis (treated with ASO). The mice were treated with ASO SREBP-1c as previously described by our group. After ASO treatment, one set of animals was anesthetized and used for in vivo test, and another mice set was anesthetized and used for histology and Western blot analysis. Reversion of diet-induced hepatic steatosis did not change blood glucose, glucose decay constant (kITT), body weight, or serum insulin levels. In addition, results showed that the protocol did not improve insulin pathway signaling, as confirmed by the absence of changes in IR, IRS1, Akt and Foxo1 phosphorylation in hepatic tissue. In parallel, no alterations were observed in proinflammatory molecules. Thus, our results suggest that the inhibition of SREBP-1c reverts steatosis, but without improving insulin hepatic resistance.
Keywords: SREBP-1c; steatosis; insulin resistance; inflammation